Evaluation of the Quality, Educational Value and Utility of the Videos on YouTube for Laparoscopic Low Anterior Resection. Issue 9 (September 2022) - Piskin, Erol; Çolakoğlu, Muhammet Kadri; Bal, Ali; Oter, Volkan; Bostanci, Erdal Birol
Background: Minimally invasive surgery is a rising trend in colorectal surgery and is on its way to becoming the gold standard due to the benefits it provides for patients. This study aims to test the efficacy for educational purposes by evaluating the videos published on YouTube (www.youtube.com ) channel for low anterior resection procedure in rectum surgery. Methods: We searched YouTube on October 17, 2020 to choose video clips that included relevant information about laparoscopic low anterior resection (LAR) for rectal cancer. Results: We included 25 academics and 75 individual videos in this study. The teaching quality of the videos was evaluated according to academic and individual videos, and it was seen that the teaching quality scores of academic videos were higher and this result was statistically significant ( P = .03). The modified Laparoscopic Surgery Video Educational Guidelines (LAP-VEGaS) criteria were found that the score was higher in individual videos ( P = .014). The median Video Power Index (VPI) value was 1.50 (range .05-347) and the mean ratio was 7.01 ± 3.52. There was no statistically significant difference between the 2 groups ( P = .443). Discussion: Video-based surgical learning is an effective method for surgical education. Our study showed that the video quality and educational content of most of the videos about the low anterior resection procedure on YouTube were low. The videos of academic origin seem more valuable than individual videos. As far as video popularity is concerned, YouTube viewers are not selective. For this reason, training videos to be used for educational purposes must be passed through a standardized evaluation filter.